An interpretative phenomenological analysis of the experience of self-harm repetition and recovery in young adults - Wadman, Ruth; Clarke, David; Sayal, Kapil; Vostanis, Panos; Armstrong, Marie; Harroe, Caroline; Majumder, Pallab; Townsend, Ellen (SAGE, 2016)
Six young adults (19–21) with repeat self-harm for over five years were interviewed about their self-harm, why they continued and what factors might help them to stop. Interpretative Phenomenological Analysis identified six themes: Keeping self-harm private and hidden; Self-harm as self-punishment; Self-harm provides relief and comfort; Habituation and escalation of self-harm; Emotional gains and practical costs of cutting; Not believing they will stop completely. Young adults presented self-harm as an ingrained and purposeful behaviour which they could not stop, despite the costs and risks in early adulthood. Support strategies focused on coping skills, not just eradicating self-harm, are required.